Is there an inverse-u relationship between financialisation and investment?: South Africa's stock market capitalisation in comparative perspective - Owen, Michael Robert (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
In recent decades, the growth and fluctuations in the financial sector have become increasingly disjointed from events in the real economy. There has been a dramatic increase in global market integration and globalisation since the 2008 financial crisis. The argument presented in the thesis shows perspective from the two general debates in Economics. The Orthodox view, which suggests there is an efficient flow of resources between people and institutions over time, supports the argument that there is a positive relationship between financialisation and economic growth. Alternatively, the Heterodox view argues that financial liberalisation fails to anticipate market effects and requires intervention in order to limit negative consequences. More recent studies have proposed an inverse-U theory between financialisation and investment, which suggests that there is a threshold, above which further financial development and financial globalisation has detrimental effects on the real economy. With South Africa being a developing country that is highly reliant on capital inflows to finance the economy, there is space for more acute research to investigate whether South Africa has surpassed this threshold. This study focusses on one aspect of this relationship, namely the relationship between Stock Market Capitalisation and Investment. It uses panel data analysis and other methods to explore whether such an inverse-U relationship exists internationally, and whether South Africa is suffering from the effects of financialisation.
Keywords: Monetary policy -- South Africa; Globalization; Economics -- South Africa; Capital movements -- South Africa; Stock exchanges -- South Africa; Investments -- South Africa; Economic development -- South Africa; South Africa Economic conditions 1991-